Pharmacotherapy of arterial hypertension in patients with psoriasis - Dodulík, Jozef; Dodulíková, Lenka; Plášek, Jiří; Ramík, Zdeněk; Vrtal, Jiří; Václavík, Jan (Journal of hypertension, 2025)
Psoriasis is a chronic systemic autoimmune disease associated with an elevated risk of developing cardiovascular disease. In patients with psoriasis, arterial hypertension treatment requires careful selection of antihypertensive drugs, as some drugs may worsen the skin manifestations of psoriasis. In this review, we summarize the available evidence regarding the risks and benefits of each group of antihypertensive drugs. We also suggest a scheme for optimizing antihypertensive treatment in patients with psoriasis, with emphasis on achieving effective control of blood pressure and cardiovascular disease, while minimizing the worsening of cutaneous manifestations. Angiotensin receptor blockers appear to be the most appropriate treatment for hypertensive patients with psoriasis, with the potential addition of calcium channel blockers if blood pressure is not adequately controlled. Alternatives are angiotensin-converting enzyme inhibitors and/or mineralocorticoid receptor antagonists. Diuretics and beta blockers are associated with greater risk of worsening of psoriatic lesions.
Keywords: Adrenergic beta-Antagonists; inhibitory ACE; hypertenze; lidé; blokátory kalciových kanálů; Antihypertensive Agents; Hypertension; antihypertenziva; psoriáza; Angiotensin Receptor Antagonists; beta blokátory; Psoriasis; antagonisté receptorů pro angiotenzin; Calcium Channel Blockers; Angiotensin-Converting Enzyme Inhibitors; Humans